2021
DOI: 10.33590/emj/20-00184
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Stroke and Coronavirus Disease (COVID-19): Where is the Evidence?

Abstract: Stroke is the second leading cause of death globally. Despite the decreasing trend in stroke mortality, its incidence and prevalence follow an upwards trajectory that is envisaged to continue for years to come. Previous literature has suggested a role for infectious disease in stroke aetiology; however, the pathophysiological basis for this has never fully been understood. Emerging infections, such as coronavirus disease (COVID-19), present new challenges that must be addressed, to prevent them from contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…33 Decreased consciousness levels have also been reported in people with large hemispheric infarction and reversible encephalopathy syndrome, suggesting brain endothelial dysfunction. 34,35 Understanding the different causes of disturbed consciousness is crucial as it may lead to a specific treatment. During the early outbreak, with health systems under significant challenges, a higher proportion of people becoming unconscious and deaths was noted in Hubei than in other parts of China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Decreased consciousness levels have also been reported in people with large hemispheric infarction and reversible encephalopathy syndrome, suggesting brain endothelial dysfunction. 34,35 Understanding the different causes of disturbed consciousness is crucial as it may lead to a specific treatment. During the early outbreak, with health systems under significant challenges, a higher proportion of people becoming unconscious and deaths was noted in Hubei than in other parts of China.…”
Section: Discussionmentioning
confidence: 99%
“…Cases with encephalitis with or without SARS­CoV­2 identified in cerebrospinal fluid have been reported, 7,32 but evidence of a direct insult to the brain is still lacking 33 . Decreased consciousness levels have also been reported in people with large hemispheric infarction and reversible encephalopathy syndrome, suggesting brain endothelial dysfunction 34,35 . Understanding the different causes of disturbed consciousness is crucial as it may lead to a specific treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines such as Tumor Necrotic Factor- (TNF-) may inhibit the fibrinolytic system leading to coagulation. 5 Compared to the non-COVID-19 population, patients with COVID-19 had a disproportionately higher stroke rate. 8 SARS-CoV-2 binds to the angiotensin-converting enzyme-2 (ACE-2) receptor to enter the human cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of infectious pathogens in causing cerebrovascular episodes have been underrated. 5,6 COVID-19 is primarily a respiratory disease. However, many reports suggest that this condition may lead to a hypercoagulability state and cause thrombotic events.…”
Section: Case Report Backgroundmentioning
confidence: 99%
“…An increase in the incidence of hemorrhagic transformation after ischemic infarcts has been observed in COVID-19 stroke patients. It has been reported that almost one in 20 patients diagnosed with COVID-19 experience a stroke thereafter (Pittams et al, 2021). The relationship between stroke and infectious diseases is complex.…”
Section: Introductionmentioning
confidence: 99%